The system of criteria and indicators of accessibility of laboratory diagnostic in the Subject of The Russian Federation - Goldberg, A S; Aleksandrova, O Yu; Zudin, A B; Shegai, M M (Problemy sotsial'noi gigieny, zdravookhraneniia i istorii meditsiny, 2024)
The modern health care is characterized by constant increasing need in laboratory tests. The quality and accessibility of laboratory diagnostics becomes one of key determinants of social well-being in aspect of maintaining population health. The purpose of the study is in developing system of criteria and indicators of accessibility of laboratory diagnostics applicable in organization of health care at the level of the Subject of the Russian Federation. The methods. The study was carried out based on principles of system approach. The methodological approach developed by Professor O. Yu. Alexandrova was applied. The analytical research methods (analysis, synthesis) were implemented. The results and discussion. The set of criteria, including three groups of measurable indicators, applicable in the field of laboratory diagnostics was developed. The original approach to determine time indicators of laboratory tests accessibility was proposed. The system can be applied as organizational technology permitting to establish specific requirements for laboratory diagnostics accessibility at the level of the Subject of the Russian Federation. These requirements can be included in local normative legal acts. The conclusions. The developed system of criteria and indicators of laboratory diagnostics accessibility can be used in development of medical care system that meets the best of characteristics and needs of particular Subject of the Russian Federation.